Teacher Pedagogical Competence and Its Role in Strengthening’s Student Self-Confidence in Indonesian Language Learning - Shania Ulfach; Wakhudin Wakhudin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to analyze the relationship between teachers' pedagogical competence and the strengthening of students' self-confidence in Indonesian language learning at the Giri Jaya Cluster, Baturraden. Using a descriptive qualitative approach with a case study method in five elementary schools, data were collected through classroom observations, in-depth interviews, and analysis of learning documents. The results of the study show a clear correlation: in schools with pedagogically competent teachers—as evidenced by student-centered lesson plans, facilitative methods, and authentic assessment students showed moderate to high levels of self-confidence; conversely, teacher-centered learning environments and limited assessment correlated with low student confidence. The practical implication is that a community of teachers within a cluster needs to be developed, where teachers who have successfully implemented innovative methods can share their experiences. This study concludes that effective pedagogical practices, such as cooperative learning, creating a safe classroom climate, and providing constructive feedback, are critical foundations for building student confidence. These findings underscore the central role of mature teaching competencies in holistic student development.